Development of Snake-D Ladd-Up Media Based On East Java Culture to Improve Cultural Literacy of Grade IV Elementary School Students - Intan Susetyo Kusumo Wardhani; Teristiana Teristiana (JURNAL PENDIDIKAN DASAR NUSANTARA, 2026)
Cultural literacy plays an important role in supporting students in understanding and appreciating cultural diversity, traditions, and societal values. Based on observations and interviews with fourth-grade teachers, it was found that the social studies learning media used lacked variety, especially in the material on regional cultural diversity, resulting in suboptimal delivery. This study aims to describe the initial condition of fourth-grade students' cultural literacy, design the Snake-D Ladd-Up media based on East Javanese culture, and test the implementation, validity, and effectiveness of the media in improving cultural literacy. This study used the Research and Development (RnD) method with the ADDIE model approach. The research instruments included interviews, observations, material validation questionnaires, media, language, practitioners, and tests validated using the Aiken v construct. The sample was determined using a purposive sampling method, involving fourth-grade students from four elementary schools. The results showed that the Snake-D Ladd-Up media was very valid with 96% of experts' scores and very practical with 94% of practitioners' scores. The average pretest and posttest results showed a significant increase from 53 to 83 on a small scale and from 55.17 to 89.15 on a field scale. Therefore, the Snake-D Ladd-Up media has been proven to help make the learning process more enjoyable, facilitate explanations, and its use does not require extensive preparation.